PENINGKATAN DISIPLIN KERJA OLEH PIMPINAN DALAM ORGANISASI - Almitraf , (Jurnal Bahana Manajemen Pendidikan, 2015)
The writing is on the background backs by the lack of effective discipline that is given by the leadership in the organization. This research aims to obtain information about: (1) It still looks employees who came late to the office. Hours to come to work at 08.00 am while employees there who came at 08.30 pm even at 09.00 am. (2) The responsibility that is less than employees in doing the work that has been given. (3) It still looks employees are less adherent to regulatory agency that is not visible from the work accomplished in accordance with the predetermined targets. (4) It still looks employees who come into the office just took a hiatus.Efforts in improving labor discipline are: (1) Negative Approach, (2) Positive Approach, (3) Disciplining Yourself, (4) Creating a safe atmosphere and (5) Providing Penalties such light sentences and penalties were severe penalties.Key word : Work Disipline